Affective adaptation = effective transformation? Shifting the politics of climate change adaptation and transformation from the status quo. (18th October 2021) - Nightingale, Andrea J.; Gonda, Noémi; Eriksen, Siri H.
Abstract: Alarming rates of environmental change have catalyzed scholars to call for fundamental transformations in social‐political and economic relations. Yet cautionary tales about how power and politics are constitutive of these efforts fill the literature. We show how a relational framing of adaptation and transformation demands a political, cross‐scalar, and socionatural analysis to probe the affects and effects of climate change and better grasp how transformative change unfolds. We bring affect theory into conversation with the literature on adaptation politics, socio‐environmental transformations, subjectivity, and our empirical work to frame our analysis around three under investigated aspects of transformation: (i) the uncertain and unpredictable relations that constitute socionatures; (ii) other ways of knowing; and (iii) the affective and emotional relations that form a basis for action. Affective adaptation represents a different ontological take on transformation by reframing the socionatural, normative and ethical aspects as relational, uncertain, and performative. This directs analytical attention to processes rather than outcomes. The emphasis on the encounter between bodies in affect theory points to the need for experiential and embodied ways of knowing climate to effect transformative change. Effective transformation requires recognizing uncertainty and unpredictability as part of transformative processes. This is not because all outcomes are acceptable, but rather because uncertainty and unpredictability are elements which help generate affects (action) and emotional commitment to shared human and more than human relations in action, projects, and policies. This article is categorized under: Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Abstract : Transformation in the face of climate change requires new human‐environment relations as symbolized by a major river gone dry in Nicaragua. Affective processes whereby change can be debated using science, emotions and experiential ways of knowing opens new political pathways to change.